PENGARUH LATIHAN KNEE-TUCK JUMP TERHADAP EXPLOSIVE POWER OTOT TUNGKAI PADA TIM BOLA VOLI PUTRA PENDOR - Rahmad, Syaizar; Juita, Ardiah; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study was conducted to determine whether there are effects of exercise on the knee-tuck jump explosive leg muscle power in volleyball game so that when doing a smash to get maximum results.This research is a form of research with experimental treatment (Experimental), with a population of athletes volleyball men’s pendor club, in this study all population data of 15 people. The instruments used in this research is vertical jump test, which aims to measure leg power in the vertical direction. Afterthat, data is processed with statistics, to the test normality of the test at significant level 0,05α lilifors.Hypothesis proposed, exercise effect of Knee-Tuck Jump To Explosive Muscle Power Limbs. Based on t test analysis produces 11,54 Thitung and 1.761 Ttabel, its means Thitung>Ttabel. Based on analysis of statistical data, there are on Pree-test average was 57,6 and post-test average was 60,6, data is normal. Then, there is a Exercise Effect of Knee-Tuck Jump To Explosive Muscle Power Limbs In Games Volleyball Men’s Pendor Club.Key-words: Knee-Tuck Jump, Explosive Muscle Power Limbs